2017
DOI: 10.1136/bmjquality.u211657.w6106
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Stickers - Improving oral hydration in vulnerable patients

Abstract: Dehydration is a growing problem among elderly patients in hospital wards. Incidents such as those raised in the Francis Report highlight a problem that may not have been sufficiently addressed by current schemes. This improvement project aimed to identify the barriers faced by staff in improving oral hydration and to design and implement an effective solution. A 33 patient pilot study carried out at Chelsea & Westminster Hospital NHS Trust, United Kingdom, revealed that a significant proportion of patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The site team noted that regular rotation and introduction of new hydration promotion posters was needed to keep up the interest of team members, family and residents. These findings are consistent with prior research, that reminders are easy to implement, however their effect is likely insufficient to change behavior (Bhatti et al, 2017;Gaff et al, 2015).…”
Section: Question (Pre-test Only)supporting
confidence: 91%
“…The site team noted that regular rotation and introduction of new hydration promotion posters was needed to keep up the interest of team members, family and residents. These findings are consistent with prior research, that reminders are easy to implement, however their effect is likely insufficient to change behavior (Bhatti et al, 2017;Gaff et al, 2015).…”
Section: Question (Pre-test Only)supporting
confidence: 91%
“…Early detection and interventions to manage dehydration could have important implications not only for older adults' health, but also for cognitive functioning, well-being, and overall quality of life. For example, it has been found that a combination of different approaches could be beneficial for combating dehydration in older adults, including easy access to and availability of different types of beverages, educating staff in residential care homes (Bunn, Jimoh, Wilsher, & Hooper, 2015), as well as using visual prompts such as high-contrast fluid containers (e.g., bright-colored cups; Dunne, Neargarder, Cipolloni, & Cronin-Golomb, 2004) and stickers or badges (e.g., "hydration stickers"; Bhatti, Ash, Gokani, & Singh, 2017) to motivate higher fluid intake among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…An effective approach was the Hydration Sticker education scheme piloted by a UK National Health Services (NHS) Trust hospital which provided visual prompts for staff and family members to encourage patient drinking and demonstrated a 6.5-fold increase in the number of patients having their hydration needs met. 21 In the UK long-term care home setting findings of a detailed fluid intake assessment in the UK Dehydration Recognition In our Elders (DRIE) study indicated intake of drinks was mostly between meals and with medications. 22 Offering water and drinks more often through the day, especially with medications, is likely to increase fluid intake as drinking needs to be driven by routine rather than reliance on patient thirst.…”
Section: Discussionmentioning
confidence: 99%